Effect of Angiotensin II Receptor Blockers and Dietary Pattern on Renal Failure for Hypertension Patients in Benghazi - Fawzia Ahmed; Ambaraka Kreim; Eman Alaqeli; Abir Ben Ashur; Hamida El Magrahi; Arij Mousa; Atia, Ahmed; Manal Abuagela; Eman Abdulwahed; Rehab Jerbi; et al. (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Libya is experiencing a rapid health transition and is projected to become a major reservoir of chronic diseases like diabetes and hypertension. About 25–40% of these subjects may develop chronic kidney disease (CKD) and end stage renal disease (ESRD). The current study was aimed at analyzing the drug utilization pattern of antihypertensive in patients with chronic kidney disease and to detect the effect of other factors such as age and diet program on hypertensive patients. Methods. A cross sectional study was conducted in patients with chronic kidney disease at the department of nephrology in Al-Hwari hospital in Benghazi city, Libya, over a period of 6 months in 2018. After obtaining the clearance and approval from the Institutional Ethics Committee, a total of 150 inpatients who gave informed consent were included in the study. The information regarding demographic details and antihypertensive drugs prescribed were collected from the patient’s case records. Descriptive statistics was done by measuring proportions using SPSS version 20. Results. It was found that 8.1% of individuals were aged between 19-25 years, 37.6% were between 26-40 years, 45.6% were 41-60 years, and 8.7% more than 60 years (M=43, SD=13). From statistical analysis we found that a significant difference between subjects who used Candesartan and other antihypertensive (p= 0.000<0,05). Related to dietary pattern, it was found that 28.9% of the patients drunk two glasses of water per day, 62.4% three glasses per day and 8.7% drank one glass per day. Conclusion. The prevalence of CKD was high in our subjects. The preferential drugs employed among antihypertensive were candesartan and telmisartan than other antihypertensive drugs. The overall impression about the prescription trends noted herein is suggestive of a modest and rational approach in prescribing practices.